Estudio de factibilidad para la implementación de una sala velatoria y servicios exequiales en el cantón Chaguarpamba. - Torres Ludeña, Darwin Vicente (2012)
The project present have like enterprise gestión in exequial serviousin the Chaguarpamba town, and sell de service should satisfy the necessities of the customer about in the meet and pagment at home however at the moment of compare necessary investment in order of get utilities but the best thing is to make more investment in the future to satisfy common market that it can`t be attended in addition the utilities are acceptables even there are lot of credits which should be canceled monthly and for the purchase of active like vehicles, equipment that are done at the be gining at the activities in the future. The referent proyect could be have a useful life of five years and it´s location will be in es Av. Vía a la Costa y strettOlmedo. To check the feasibility of the present project he/she is carried out the market study using the field investigation, technical of scientific investigation as: bibliographical, of observation, surveys and 183 persons interviews, the same ones that allowed obtaining information related with the demand and the offer. The company is update in the tributary duties, politic labor, patronal, performancing, with present economic politics of the government. In relation to the organization of the company it is of limited responsibility and will be confirmed by the general group of members, boss, attoney, secretary, accountant, and the staff needed to the process of service . In the administration of the Company problems can settle down among which can highlight the lack of incentives for clients, training of the personnel in attention to the client. These aspects are necessary that they are overcome to be able to optimize the profitability of the company on mention. For the economics calculator development of the present work the methodology was continued that corresponds to a strategic plan, he/she was also defined the internal and external conditions by means of the use of the invention of $60.887,67 those that it allowed us to know the situation of the company objectively VAN of $25.684,83, and a relation cost – benefit of 1.50, an a TIR of 24.42% of security invention. The conclusions are be of objectives of projectInside this work one also carries out an I diagnose situational, through the external analysis and I intern of the company information that served like base to apply those in hills to lectors the internal and external actors of the same one.